Financial and non-financial factors motivating individual donors to support public benefit organizations - Halina Waniak-Michalak; Ewelina Zarzycka (Comparative Economic Research. Central and Eastern Europe, 2015)
This study is aimed at determining how the financial data of public benefit organizations (PBOs) affects donations received by them and if the donors use financial and non-financial information in order to donate. In order to achieve our aim we used different methods of research: quantitative research (econometric model and survey) and qualitative research (laboratory test). The research allowed us to draw the conclusion that Polish donors make very limited use of PBOs' financial statements in the donation process and that non-financial information plays greater role for donors in making decisions to give charitable donations. The most important information is the organization's goals and descriptions of its projects. At the same time, many donors stated that they donated under the influence of people they knew. This article fits into the scope of world research on PBOs and uses the concept of civil society.
Keywords: 330; Public Benefit Organisations; Performance measurement; donors